Sanksi Atas Kelalaian Penyampaian Laporan Keuangan Bagi Perusahaan Publik Dalam Perdagangan Saham Di Bursa Efek Indonesia dan Akibat Hukum Terhadap Pengelolaan Perusahaan; Studi Kasus Suspensi Saham PT Tiga Pilar Sejahtera Food Tbk - Sari Fitria Ningrum; Ahmad Chaerul Hadi (JOURNAL of LEGAL RESEARCH, 2019)
Abstract.Failure to submit financial statements is a form of violation in the capital market. This research is a case study of PT Tiga Pilar Sejahtera Food Tbk's stock suspension which refers to the Indonesian Company Law and the Indonesian Company Law. The approach used in this study is a normative approach through library research with qualitative research methods. The results of this study are the forms of violations committed by PT Tiga Pilar Sejahtera Food Tbk in the form of negligence in submitting financial statements in 2017-2018. The legal consequence of negligence in submitting financial statements is the sanction imposed by the Indonesia Stock Exchange on companies in the form of fines and suspension of shares of PT Tiga Pilar Sejahtera Food Tbk (AISA). In addition, shareholders exercise their right to dismiss directors.Keywords: Information Openness, Good Corporate Governance, Fiduciary Duty, Stock Suspension Sanctions.